Reversible [4 + 2] cycloaddition reaction of 1, 3, 2, 5-diazadiborinine with ethylene. Issue 12 (24th September 2015) - Wu, Di; Ganguly, Rakesh; Li, Yongxin; Hoo, Sin Ni; Hirao, Hajime; Kinjo, Rei
Abstract : Under ambient conditions, a [4 + 2] cycloaddition reaction of 1, 3, 2, 5-diazadiborinine1 with ethylene afforded a bicyclo[2.2.2] derivative2, which was structurally characterized. Abstract : Under ambient conditions, a [4 + 2] cycloaddition reaction of 1, 3, 2, 5-diazadiborinine1 with ethylene afforded a bicyclo[2.2.2] derivative2, which was structurally characterized. The cyclization process was found to be reversible, and thus retro-[4 + 2] cycloaddition reproduced1 quantitatively, concomitant with the release of ethylene. Compound1 reacted regio-selectively and stereo-selectively with styrene derivatives and norbornene, respectively, and these processes were found to be reversible too. Computational studies determined the reaction pathways which were consistent with the regio-selectivity observed in the reaction of styrene, and the reaction was suggested to be essentially concerted but highly asynchronous.